Hvad er opstandelseslegemets karakter ud fra Første Korintherbrev 15? - Mikkelsen, Daniel (Dansk Teologisk Tidsskrift, 2019)
The article examines the character of the resurrection body in 1 Corinthians 15,36-58 focusing on exegesis and vocabulary. The examination pays special attention to the two most dominating views of the resurrection body in recent scholarly debate, the resurrection of re-newed flesh and the resurrection in pneumatic material. The article has three parts. Since both views attend to much of the same terminology, a clarification of their terminology is first given. Next, the exegetical dif-ferences between them are lined up against one another. Finally, an ex-egesis is given which argues that Paul is not talking about a resurrection body composed of ethereal material spirit, but about a body composed of flesh whose state and quality have changed so that it becomes both incorruptible and immortal. This is because the reason for the corrup-tion of the flesh is Adam’s fall and sin, not the flesh itself.